2018
DOI: 10.18203/2320-6012.ijrms20180427
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive evaluation of conventional anticonvulsant with conventional analgesics on pain model of albino rats and mice

Abstract: Background: Pain is one of the most common presentations of any disorder and needs immediate and appropriate attention of the treating physician. As pain syndrome involves a variety of etiopathogenesis and temporal domains, management of pain as such requires consideration of many factors that may dictate appropriate therapeutic management. Carabmazepine is an established drug for trigeminal neuralgia while Gabapentin has been tried in postoperative pain but its effectiveness per se and when compared to conven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
2
1
Order By: Relevance
“…This conflict can be explained on the basis of lower oral doses used in Kansal's study 50mg/kg while in the current study higher doses of gabapentin 100mg/kg were used. Regarding diclofenac, the results of the present study are combatable with that of Agarwal and Kansal, (20) who found that diclofenac, at a dose of 5, 10 and 20mg/kg, i.p., produced significant analgesic effect in formalin test, both in phase (1 and 2). Concerning tizanidine, results of the present study cope with that obtained with Yazicioglu et al, (21) who concluded that the addition of tizanidine in postoperative pain therapy decreased postoperative pain, analgesic consumption and improved the return to normal activity.…”
Section: Table (3): Percentage Changes In the Mrt Compared To The Post-carragenan Control After Ip Injection Of {Gabapentin (100 Mg/kg) +contrasting
confidence: 52%
“…This conflict can be explained on the basis of lower oral doses used in Kansal's study 50mg/kg while in the current study higher doses of gabapentin 100mg/kg were used. Regarding diclofenac, the results of the present study are combatable with that of Agarwal and Kansal, (20) who found that diclofenac, at a dose of 5, 10 and 20mg/kg, i.p., produced significant analgesic effect in formalin test, both in phase (1 and 2). Concerning tizanidine, results of the present study cope with that obtained with Yazicioglu et al, (21) who concluded that the addition of tizanidine in postoperative pain therapy decreased postoperative pain, analgesic consumption and improved the return to normal activity.…”
Section: Table (3): Percentage Changes In the Mrt Compared To The Post-carragenan Control After Ip Injection Of {Gabapentin (100 Mg/kg) +contrasting
confidence: 52%
“…Pain has an inflammatory component. In our research, flunixin meglumine has demonstrated important analgesic and anti-inflammatory effects in chicks (using the formalin test).The formalin test is being used as an inflammatory model of tonic pain [24]. Subcutaneous paw injecting of formalin causes biphasic nociceptive reactions.…”
Section: Discussionmentioning
confidence: 95%
“…As such, the acetic-acid induced writhing test was used to further evaluate the analgesic effect of ZAE. This model is known to implicate both visceral and inflammatory pain ( Agarwal and Kansal, 2018 ). Intraperitoneal injection of acetic acid is known to activate pain sensation through a localized inflammatory response leading to the release of free arachidonic acid from tissue phospholipids via the activity of cyclooxygenase leading to increased production of prostaglandins (PGE 2 and PGF 2 ) in peritoneal fluids ( Uddin et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%